2021
DOI: 10.1021/acsomega.0c06288
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Reverses Breast Cancer Multidrug Resistance Based on Fluorescence Pharmacokinetics In Vitro and In Vivo

Abstract: Exploring the mechanism through which berberine (Ber) reverses the multidrug resistance (MDR) of breast cancer is of great importance. Herein, we used the methyl thiazolyl tetrazolium assay to determine the drug resistance and cytotoxicity of Ber and doxorubicin (DOX) alone or in combination on the breast cancer cell line MCF-7/DOX Fluc . The results showed that Ber could synergistically enhance the inhibitory effect of DOX on tumor cell proliferation in vitro , an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In addition, the combination of berberine with chemotherapeutic drugs (cisplatin and 5-fluorouracil) showed synergistic effects on suppressing breast cancer cell proliferation, thus inducing apoptosis and inhibiting cell migration [ 40 , 41 ]. Anyway, berberine could reverse the multidrug resistance of breast cancer by suppressing the efflux function of ATP-binding cassette transporters [ 42 ].…”
Section: Effects Of Berberine On Cancersmentioning
confidence: 99%
“…In addition, the combination of berberine with chemotherapeutic drugs (cisplatin and 5-fluorouracil) showed synergistic effects on suppressing breast cancer cell proliferation, thus inducing apoptosis and inhibiting cell migration [ 40 , 41 ]. Anyway, berberine could reverse the multidrug resistance of breast cancer by suppressing the efflux function of ATP-binding cassette transporters [ 42 ].…”
Section: Effects Of Berberine On Cancersmentioning
confidence: 99%
“…Studies have shown that BBR can increase the level of reactive oxygen species (ROS) to induce apoptosis in lapatinib-resistant cells and reverse the drug resistance of breast cancer cells ( Zhang et al, 2016 ). In addition, BBR and Dox synergistically enhanced the inhibitory effect on cancer cells by reducing P-gp and multidrug resistance protein 1 expression with the best BBR/Dox ratio of = 2:1 ( Qian et al, 2021 ).…”
Section: Mechanisms Of Bbr Anticancer Effectsmentioning
confidence: 99%
“…BBR is also used as a potential agent for breast therapy due to its ability to reverse MDR. Therefore, combinations of natural products showed robust effects in reducing invasion, migration, and the EMT process [ 122 , 123 ].…”
Section: Synergistic Approach Of Natural Products Against Bcmentioning
confidence: 99%